Estimating the uptake of maternal syphilis screening and other antenatal interventions before and after national rollout of syphilis point-of-care testing in Ghana. (June 2015) - Dassah, Edward T.; Adu-Sarkodie, Yaw; Mayaud, Philippe
Abstract: Objective: To compare the uptake of maternal syphilis and HIV screening, intermittent preventive treatment for malaria, and tetanus toxoid administration in three regions of Ghana, before and after the rollout of syphilis point-of-care tests (POCTs). Methods: Antenatal register records were reviewed in 15 selected health facilities over an eight-month period, 16 months apart. Register records had been evaluated using the maternal record booklets as a gold standard in a separate prior survey. Results: In the evaluation study, the sensitivity of register data was low, ranging from 33.3% for tetanus toxoid administration to 53.8% for syphilis serology. In total, 8282 antenatal client records (4141 in each period) were reviewed. Less than a third of pregnant women received any single intervention at either period (ranging from 17.8% for tetanus toxoid to 29.8% for HIV testing). Overall, HIV screening had a marginal absolute increase of about 2% while the remaining interventions experienced non-significant absolute decreases of 4.1 to11.1%. When adjusting for under-recording, syphilis screening uptake was 50% before and 33.6% after the introduction of POCTs. Conclusion: Use of POCTs for syphilis did not result in increased uptake. Routine monitoring of antenatal interventions using the antenatal register may result in underestimation of their uptake.